Effects of Different Diet Types on Growth and Survival of White-Clawed Crayfish Austropotamobius pallipes in Hatcheries - Nightingale, Jen; Jones, Gareth; McCabe, Gráinne; Stebbing, Paul (Frontiers in Ecology and Evolution, 2021)
Developing an optimal diet for rearing endangered white-clawed crayfish Austropotamobius pallipes is important for captive breeding success prior to wild release. Four ex-situ, 40-day experiments assessed survival and growth of crayfish fed different treatment diets. Two experiments (A & B) were undertaken with hatchlings, to determine if live food was an essential dietary component during the first few weeks after hatching. The second set of experiments (C & D) were undertaken with juvenile (60-day-old) A. pallipes, to determine an optimal diet after the initial critical feeding stage. In experiment A, we fed hatchlings: i) live Artemia nauplii + plankton (Live+P); ii) decapsulated Artemia cysts + plankton (Cyst+P) or iii) decapsulated Artemia cysts + plankton encapsulated in agar gel (Gel+CP). Survival and growth was significantly greater with Live+P than with the other two diets. In Experiment B we compared Live+P with commercially available feeds by feeding hatchlings: i) live Artemia nauplii + Australian pellet (Live+Aus); ii) live Artemia nauplii plus New Zealand pellet (Live+NZ); iii) live Artemia nauplii + plankton (Live+P); or (iv) practical Spanish crayfish pellet diet (Spain). Under these experimental conditions crayfish survival was significantly higher with Live+P diet than with Live+Aus or Spain. Growth was also significantly greater with Live+P than with the Live+NZ or Spanish treatment diets. In experiment C, 60-day-old juvenile A. pallipes were fed: i) defrosted plankton plus vegetables (Standard) or (ii) defrosted plankton plus vegetables encapsulated in agar gel (Gel+PV). Survival was not significantly different between the diets; however, growth was significantly greater with the Standard diet rather than Gel+PV. In experiment D, juveniles were fed four different diets: i) Australian pellet (Australia); ii) New Zealand pellet (New Zealand); iii) plankton and vegetables (Standard); or iv) practical Spanish diet (Spain). Survival was significantly lower in crayfish fed the New Zealand diet. Crayfish growth was significantly greater with the Standard diet of plankton and vegetables than all three pellet diets. Our results showed that live food is optimal for high survival and growth in A. pallipes hatchlings and a plankton, plus vegetable, diet produces higher growth in juveniles compared to pellet diets.